G529(P) Flow rate as a predictor of weaning home oxygen in babies with bronchopulmonary dysplasia. (27th April 2016) - Millard, K; Hurley, M; Prayle, A; Batra, D; Bhatt, JM
Abstract : Aims: There are currently no evidence-based guidelines available to assist in the weaning of home oxygen for babies with bronchopulmonary dysplasia (BPD). Our local care pathway follows a programme of weaning under which babies come off oxygen after reaching a flow rate of 0.1 l/min and maintaining saturations of 93% or above for a period of 2 h in air. Previous small studies have suggested that flow rates of less than 20cm 3 /kg/min may be a predictor of success in coming off oxygen. The aim of this study was to explore the flow rates in babies ready to come off oxygen. Methods: All babies known to our tertiary respiratory service born between April 2007 and May 2015, and who had successfully weaned from home oxygen for BPD were included (n = 156). The date oxygen is stopped is prospectively recorded. Weight at the time of coming off oxygen was established from the patient records and used to calculate flow rates in cm 3 /kg/min. Twenty-four babies were excluded as the weight at the time of stopping oxygen was not available. Results: 132 babies were included in the analysis. Mean weight at cessation of home oxygen was 6.61kg (SD 1.75kg), with a mean flow rate of 16.27cm 3 /kg/min (SD 4.65 cm 3/ kg/min). Flow rates in 109/132 babies (82.5%) were <20 cm 3 /kg/min at the time of successful weaning. Conclusion: Successful weaning from home oxygen in a large cohort of babies with BPD is associated with pre-weaning flow rates of less than 20cm 3 /kg/min. This confirms previous suggestions that this may be a useful predictor of readiness to come off oxygen. We are planning to prospectively validate whether the flow rate based on weight is a useful indicator of readiness to wean from oxygen.